The Readiness of the Laboratories of the College of Science at the Northern Border University to Activate the use of Virtual Laboratories from the point of view of Faculty Members - Alanazi, Tarfa Hamdi Khalif; Alshehri, Ajlan Mohammed Houjeer (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the requirements to activate the use of virtual laboratories in the College of Science at the Northern Border University in the Kingdom of Saudi Arabia, and to identify the most prominent obstacles that limit the activation of their use from the point of view of faculty members. The study population consisted of (317) faculty members, who were chosen by the stratified random method. The study employed the descriptive analytical method. The study tool consisted of a questionnaire consisting of (28) items in its final form, distributed on five axes of requirements (technical- human- organizational- functional) in addition to an open question. The results showed that the technical requirements came to a high degree with an arithmetic average (3.58 out of 5), the human requirements came to a moderate degree with an arithmetic mean (3.158), the organizational requirements came to a moderate degree with an arithmetic mean (3.309), and the functional requirements came to a moderate degree with an arithmetic mean (3.378). The results also showed that there are obstacles to activating the use of virtual laboratories in the laboratories of the College of Science at the Northern Border University, with a moderate degree, with an arithmetic mean of (3.18), and they were: the weakness of the Internet and its frequent interruptions, the large number of students, the lack of a guide for safety instructions in the virtual laboratories, and the structure The communications infrastructure is not developed, it is difficult to coordinate with the deanships, and the available computers have ineffective specifications for using the virtual laboratories. In light of this, the study recommended developing the telecommunications infrastructure and strengthening the Internet in the laboratories of the Faculty of Science at the Northern Border University.
Keywords: Readiness; Virtual Laboratories; faculty of Science; Faculty Members